2019
DOI: 10.1371/journal.pone.0217464
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing innovators: Ecological and individual predictors of problem-solving performance

Abstract: Behavioural innovation, the use of new behaviours or existing ones in novel contexts, can have important ecological and evolutionary consequences for animals. An understanding of these consequences would be incomplete without considering the traits that predispose certain individuals to exhibit innovative behaviour. Several individual and ecological variables are hypothesized to affect innovativeness, but empirical studies show mixed results. We examined the effects of dominance rank, exploratory personality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 65 publications
(110 reference statements)
0
19
0
Order By: Relevance
“…This could possibly improve problem solving abilities of juveniles despite their lack of experience at solving tasks. However, results are species-specific, as Indian mynas [ 173 ] and spotted hyenas [ 174 ] show no age-specific effects on problem solving in foraging tasks, while adult meerkats [ 27 ] and black-capped chickadees [ 175 ] were better innovators than juveniles in extractive foraging tasks.…”
Section: Interacting Factors That Influence the Development Of Promentioning
confidence: 99%
“…This could possibly improve problem solving abilities of juveniles despite their lack of experience at solving tasks. However, results are species-specific, as Indian mynas [ 173 ] and spotted hyenas [ 174 ] show no age-specific effects on problem solving in foraging tasks, while adult meerkats [ 27 ] and black-capped chickadees [ 175 ] were better innovators than juveniles in extractive foraging tasks.…”
Section: Interacting Factors That Influence the Development Of Promentioning
confidence: 99%
“…In the past decade, a series of studies focusing on various bird species found general support for enhanced problem-solving abilities of populations in urban over more natural areas (e.g. [11][12][13][14]). The underlying mechanisms of problem-solving differences are poorly understood.…”
Section: Backroundmentioning
confidence: 99%
“…In addition, an animal's performance might be influenced by persistence (i.e. the number of solving attempts or time spent manipulating the task set-up) [14]. Furthermore, the inability to perform a motor action or the ability to stop a non-successful action could cause differences in problem-solving performance [17,18].…”
Section: Backroundmentioning
confidence: 99%
“…This flexibility in ARTs is uncoupled from personality (Yuen et al 2015) and possibly also cognition, such a problem-solving. Problem-solving is not a fixed cognitive trait and can change via social learning (e.g., Aplin et al 2015) or because of environmental changes (e.g., Prasher et al 2019). Such potential intrinsic and extrinsic influences suggest changes in problem-solving within an individual's lifetime.…”
Section: Discussionmentioning
confidence: 99%